2016
DOI: 10.1002/jbt.21817
|View full text |Cite
|
Sign up to set email alerts
|

Morin Hydrate Mitigates Cisplatin‐Induced Renal and Hepatic Injury by Impeding Oxidative/Nitrosative Stress and Inflammation in Mice

Abstract: Cisplatin is a widely used chemotherapeutic drug; however, it induces damage on kidney and liver at clinically effective higher doses. Morin hydrate possesses antioxidant, anti-inflammatory, and anticancer properties. Therefore, we aimed to investigate the effects of morin hydrate (50 and 100 mg/kg, orally) against the renohepatic toxicity induced by a high dose of cisplatin (20 mg/kg, intraperitoneally). Renal and hepatic function, oxidative/nitrosative stress, and inflammatory markers along with histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, the adverse events associated with cisplatin treatment, which occur in 28% to 36% of patients, limit its efficacy, many times resulting in the prolongation of treatment cycles. The kidneys and the liver are two of the organs where cisplatin accumulates, frequently leading to nephrotoxicity and hepatotoxicity (Gao et al, 2017;Isoda et al, 2018;K v et al, 2016). Moreover, the toxicity profile of cisplatin significantly reduces patient survival and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adverse events associated with cisplatin treatment, which occur in 28% to 36% of patients, limit its efficacy, many times resulting in the prolongation of treatment cycles. The kidneys and the liver are two of the organs where cisplatin accumulates, frequently leading to nephrotoxicity and hepatotoxicity (Gao et al, 2017;Isoda et al, 2018;K v et al, 2016). Moreover, the toxicity profile of cisplatin significantly reduces patient survival and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Compensation of these adverse effects can be achieved by combination treatment with a drug, which would reduce the systemic toxicity by acting as an antioxidant or by allowing to decrease the required dose of chemotherapeutic agent [24]. In fact, it has been proven that morin treatment along with cisplatin significantly mitigated the negative influence of cisplatin on liver [37] and kidney function [7, 37, 38], through the reduction of oxidative stress, inflammation and apoptosis [7]. On the other hand, we (along with many others) have demonstrated that morin sensitizes various cancer cells to chemotherapeutic agents, what may allow to decrease the required doses in clinical treatment in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Second , this is not the only possible action of morin inside cells. This flavonol also acts as an antioxidant, which reduces oxidative stress [7, 37]. The activity may be achieved due to the presence of the hydroxyl groups attached at various positions in its characteristic flavonoid structure, which can directly scavenge the reactive species [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 19 potential compounds, including saikosaponin c_qt, quercetin, kaempferol and chrysazin, Luteolin, beta-sitosterol, isorhamnetin, curcolactone, stigmasterol, 2-methoxy-9,10-dihydrophenanthrene-4,5-diol, areapillin, morin, 3,5,6,7-tetramethoxy-2-(3,4,5-trimethoxyphenyl) chromone, delphinidin, troxerutin, cubebin, α-spinasterol, linoleyl acetate and vulgaxanthin-I might play the key role in LRK-treated HMG. Studies showed that most of those potential active ingredients have anti-inflammatory or anti-oxidative effects, such as quercetin, ( Song et al, 2018 , kaempferol ( Huang et al, 2018 ; Wang J. et al, 2018 ), Luteolin ( Aziz et al, 2018 ), beta-sitosterol ( Liao et al, 2018 ), isorhamnetin ( Qiu et al, 2016 ), delphinidin ( Wang et al, 2017 ), troxerutin ( Najafi et al, 2018 ), cubebin ( Bastos et al, 2001 ), morin ( Athira et al, 2016 ), linoleyl acetate ( Peana et al, 2002 ) have anti-inflammatory effects. Compounds like quercetin ( Sherif, 2018 ), kaempferol ( Kouhestani et al, 2018 ), Luteolin ( Yang et al, 2018 ), beta-sitosterol ( Yin et al, 2018 ), delphinidin ( Cheol et al, 2016 ), troxerutin ( Farajdokht et al, 2017 ), morin ( Ma et al, 2016 ), linoleyl acetate ( Peng et al, 2014 ) showed anti-oxidative stress effect.…”
Section: Discussionmentioning
confidence: 99%